2010
DOI: 10.1097/brs.0b013e3181caa86c
|View full text |Cite
|
Sign up to set email alerts
|

Complicated Surgical Resection of Malignant Tumors in the Upper Cervical Spine After Failed Ion-Beam Radiation Therapy

Abstract: Severe complications, mainly associated with the disturbance in healing of the retropharyngeal wall, were observed in all 3 patients. A preventive method, such as primary repair of the retropharyngeal wall using muscular/musculocutaneous flaps, should be considered for patients undergoing resection through a transoral approach after ion-beam irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Although surgical/biopsy pathway recurrences and subcutaneous metastasis are likely to benefit from a radical treatment with curative intent based on en bloc wide resection and/or a new full dose irradiation, nodal as well as prevertebral and leptomeningeal recurrences associated with cervical primaries, as in our series, are rarely accessible to a second radical treatment, such as surgery or reirradiation.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Although surgical/biopsy pathway recurrences and subcutaneous metastasis are likely to benefit from a radical treatment with curative intent based on en bloc wide resection and/or a new full dose irradiation, nodal as well as prevertebral and leptomeningeal recurrences associated with cervical primaries, as in our series, are rarely accessible to a second radical treatment, such as surgery or reirradiation.…”
Section: Discussionmentioning
confidence: 79%
“…7,8 Treatment options for local recurrences include reirradiation and reoperationwith a high morbidity. [9][10][11][12] However, the ectopic recurrence patterns are rarely described within remote structures, such as regional lymph nodes, surgical/biopsy pathway, and distant viscera, which account for 3%, 4.5%, and 20% of the total failures observed in the largest series, respectively. 8 Surgical/biopsy pathway recurrence occurs as a result of direct implantation of the tumor into adjacent tissue during the transit of instruments and tissue during the surgery.…”
Section: Relapse Of Chordomas and Their Prognosismentioning
confidence: 99%
“…The approach-related complication rate was 2.4%, which was lower than that reported by Traynelis 7 (12.9%), who performed the subaxial anterior approach, and lower than those who performed the retropharyngeal approach (range, 12%-20%). 13,16,[45][46][47][48] The results of the current series proved that the subaxial anterior approach could provide adequate and safe exposure for decompression and instrumentation at C2 in patients with a mandible angle higher than the C3 superior endplate on lateral extension cervical radiographs. However, the subaxial anterior approach may not be limited in these patients.…”
Section: Discussionmentioning
confidence: 93%
“…The log-rank test demonstrated that upper-level cervical chordomas are related to a worse prognosis, which is a finding supported by various reports in the literature. 29,39 It is well known that clear exposure in the upper cervical region is more challenging than in the lower cervical region, 26,38 and therefore complete resection of the tumor tissue can be very difficult sometimes due to the complicated nearby structures. In our series, incomplete tumor removal was detected in 2 patients (Cases 1 and 9) in whom tumors were present in the upper cervical vertebrae.…”
Section: Discussionmentioning
confidence: 99%